PENGENALAN MINI JURNALISTIK DALAM PEMBELAJARAN BAHASA JEPANG DI LPK TULUNGAGUNG - Mukti, Rr. Savira Ayu; Roswantoro Putra, Dimitry Julian; Darni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine students' responses in accepting new things related to mini-journalism using Japanese and at the same time determine students' abilities in implementing mini-journalism activities in Japanese. This research was carried out at one of the Job Training Institutes (LPK) Tulungagung Regency, East Java. The research subjects were LPK Tulungagung students in the Kaiwa class. Meanwhile, the object of the research is the recording of students conveying simple news using Japanese. This research method is descriptive qualitative with data collection techniques in the form of observation and documentation. The results of this research skaiwa that from a journalistic perspective, there are students kaiwa understand the basics of journalism well enough so that kaiwa carrying out assignments, these students can present news quite well and creatively. Kaiwaever, there are still students kaiwa are considered not to fully understand the elements of news, so the presentation of the news cannot be described as detailed. Meanwhile, in terms of language, it is considered quite effective but not too significant.